ANALISIS SANKSI PIDANA PELAKU ZINA DALAM PERSPEKTIF FIQIH JINAYAH - Matondang, Maulidya Mora; Agustin, Nela; Solin, Putri Nabila Aryhati; Reisyah, Karin; Najwa, Artika; Halimah, Nur (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Committing adultery is not only a violation of sharia, but also a violation of social and legal norms. This shows that the act of adultery not only has an impact on the individuals involved but also has far-reaching consequences for the life of society and the state. Where the impact of adultery is very broad, including unclear lineage for children born from adultery, increasing the complexity of social problems, decreasing human values, and damage to the social order. Adultery is seen as sexual relations outside of legal marriage. This research is research with a normative juridical approach, using library data collection methods (library research) by collecting books or references related to study.